Estudo de uma coleção de Siphonophora calycophorae da região norte-nordeste do Brasil - Nogueira, Catarina Silva Ramis (1977)
A study has been made of the systematic and zoogeographical distribution of Siphonophora Calycophorae in 101 hauls, made in the region of Notth-Northeast of Brazil, from 6°N to 8°S and from 32ºw to 52°w ; during the Oceanographic Expedition Norte-Nordeste II, by the Oceanographic Ship Almirante Saldanha, from April to June 1968. A total of 17 species was indentified, their distribution was correlated to the depht and the existing water masses in the area. By means of the hydrological data collected, it has been verífied the existence of the most atundant and frequent species in each water mess.